Pengembangan Aplikasi Mobile untuk Pencatatan Transaksi BRI Link Mini ATM Bersama Vika Cell - riski pandinata; M Abu Jihad Plaza R (Jurnal Sintaks Logika, 2026)
The growth of digital financial services through BRILink agents like Vika Cell has facilitated public transactions; however, administrative management often still relies on manual ledger entries. This conventional method entails risks such as data entry errors, delays in data recapitulation, and the potential loss of daily transaction records. This study aims to design and develop a mobile application for recording BRILink Mini ATM Bersama transactions at Vika Cell, thereby digitizing the bookkeeping system to enhance effectiveness, speed, and accuracy. The Rapid Application Development (RAD) method was employed for system development. System functionality was verified using Black-Box Testing to ensure all features operate correctly and without errors. The study resulted in a mobile-based recording application capable of managing transaction data, automatically calculating profit commissions, and generating periodic financial reports in real-time. Implementation of this application successfully minimized the risk of human error and accelerated the daily operational evaluation process.